2020
DOI: 10.1093/schizbullopen/sgaa007
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and Comorbid Opioid Use Disorder: Characteristics and Outcomes in Opioid Substitution Therapy

Abstract: Background and Objectives Substance use disorders are highly prevalent among individuals with psychotic disorders and are associated with negative outcomes. This study aims to explore differences in characteristics and treatment outcomes for individuals with psychotic disorders as compared to individuals with other non-psychotic psychiatric disorders enrolled in treatment for opioid use disorder (OUD). Methods Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Unfortunately, individuals with schizophrenia tend to receive reduced medical care and access to treatments, including comorbid OUD 33,34 . At the same time, when engaged in treatment for OUD with MAT, persons with schizophrenia generally respond favourably and remain in treatment 35 . Because of the significant heterogeneity and limitations among the 7 studies included in the systematic review, we cannot offer novel recommendations for individuals with OUD and comorbid schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, individuals with schizophrenia tend to receive reduced medical care and access to treatments, including comorbid OUD 33,34 . At the same time, when engaged in treatment for OUD with MAT, persons with schizophrenia generally respond favourably and remain in treatment 35 . Because of the significant heterogeneity and limitations among the 7 studies included in the systematic review, we cannot offer novel recommendations for individuals with OUD and comorbid schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 At the same time, when engaged in treatment for OUD with MAT, persons with schizophrenia generally respond favourably and remain in treatment. 35 Because of the significant heterogeneity and limitations among the 7 studies included in the systematic review, we cannot offer novel recommendations for individuals with OUD and comorbid schizophrenia. At the same time, 21 At present, the recommended pharmacological treatment for OUD is opioid agonist therapy (OAT) with buprenorphine or methadone.…”
Section: Figmentioning
confidence: 99%
“…Comparing individuals with an SMI alone versus those with co‐occurring OUD and SMI poorer outcomes including more severe psychiatric symptoms and higher rates of hospitalization and incarceration were seen among the OUD and SMI individuals (Lamont et al, 2020).…”
Section: Co‐occurring Opioid Use Disorder and Serious Mental Illnessmentioning
confidence: 99%
“…An emerging body of evidence suggests that MAT may not only improve substance use outcomes but may also improve mental health outcomes in individuals with co-occurring diagnosis. For example, a study investigating methadone maintenance treatment found that a diagnosis of a psychosis spectrum disorder was associated with fewer opioid-positive drug screens and comparable retention rates in the program compared to individuals suffering from an OUD but not psychosis spectrum disorder (Lamont et al, 2020). In the criminal justice system, adults with OUD and SMI who received MAT showed significant reductions in inpatient mental health treatment, inpatient substance abuse treatment, and improved adherence to psychotropic medications (Robertson et al, 2018).…”
Section: Pharmacolog Ic Al Tre Atmentmentioning
confidence: 99%
“…Additionally, polysubstance use, including substances used alongside OAT opioids, is common among OAT patients, with a prevalence of up to 70 % in this population [24,25]. While OAT may protect against suicide [9,10], polysubstance use is often a substantial contributor to reduced quality of life, homelessness, greater psychological distress, poorer social functioning, and mental disorder comorbidities -such as major depressive symptoms and borderline personality disorder [24,[26][27][28][29][30][31]. This places OAT patients at a high lifetime risk of attempting suicide [22].…”
Section: Introductionmentioning
confidence: 99%